2022
DOI: 10.1175/jtech-d-21-0103.1
|View full text |Cite
|
Sign up to set email alerts
|

SLA-Based Orthogonal Parallel Detection of Global Rotationally Coherent Lagrangian Vortices

Abstract: In this paper, we present a highly effective orthogonal parallel algorithm for identifying global rotationally coherent Lagrangian vortices (RCLVs) in heterogeneous systems and a long-time-scale global SLA-based RCLVs product. First, a manycore parallel computing method is used to accelerate the Lagrangian-averaged vorticity deviation (LAVD) computing process. The computation is approximately 8000 times faster than that of a previous method. Second, the global LAVD field is divided into several regions. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…To make such an assumption, Lagrangian coherence metrics can be used, but they are computationally expensive and rarely invoked for biophysical interpretations, with a few exceptions. He et al (2022) found chl a aggregations in coherent cyclonic eddies, and low chl a in coherent anticyclones of the Northwest Pacific. Hernández-Carrasco et al (2023) found that Lagrangian coherent eddies favor diatom growth in the oligotrophic Mediterranean Sea.…”
Section: Lagrangian Coherency Detection From Satellite Altimetrymentioning
confidence: 85%
See 2 more Smart Citations
“…To make such an assumption, Lagrangian coherence metrics can be used, but they are computationally expensive and rarely invoked for biophysical interpretations, with a few exceptions. He et al (2022) found chl a aggregations in coherent cyclonic eddies, and low chl a in coherent anticyclones of the Northwest Pacific. Hernández-Carrasco et al (2023) found that Lagrangian coherent eddies favor diatom growth in the oligotrophic Mediterranean Sea.…”
Section: Lagrangian Coherency Detection From Satellite Altimetrymentioning
confidence: 85%
“…The latter two are thought to enhance "monopole" chl a anomalies, where elevated or depressed levels of chl a are located in the core of an eddy. Satellite observations have revealed chl a monopoles in eddies shed from the Gulf Stream and other western boundary currents (Waite et al, 2007;Gaube et al, 2013Gaube et al, , 2014He et al, 2022), the Agulhas rings (Lehahn et al, 2011;Villar et al, 2015), the North Pacific Ocean (Calil and Richards, 2010;Guo et al, 2017;He et al, 2022), the South Indian Ocean (Gaube et al, 2014), and the Southern Ocean (Dawson et al, 2018;Frenger et al, 2018). Disentangling the contributions of eddy trapping and pumping to chl a monopoles remains a challenge, in part because dynamical trapping is difficult to quantify.…”
Section: Mesoscale Features In Remotely Sensed Chlorophyll Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although a small amount of filaments exists, the RCLV defined by CD < 0.1 can basically trap the initial water parcels and maintain the coherent structure over the lifetime. It is clear that, the thresholds of 0.25 and 0.01 (adopted by Tian et al, 2022) will greatly overestimate and underestimate, respectively, the size of the coherent eddy. This parameter combination has been employed successfully in our previous studies (Liu et al, 2019(Liu et al, , 2022a.…”
Section: Lagrangian Eddy Identificationmentioning
confidence: 99%
“…Based on numerical model outputs, Xia et al (2022) used the three-dimensional LAVD method to detect global coherent eddies, and they estimated the coherent transport across each latitude or longitude to be only about 1 Sv. Tian et al (2022) also applied the LAVD method to global eddy detection and presented a 90-day RCLVs dataset, but they adopted a very tight threshold to define the eddy boundary (Tarshish et al, 2018), which would greatly underestimate the size of Lagrangian eddies (see Figure 4). Nearly all public global eddy datasets are based on the Eulerian framework, and identifying coherent eddies is not an easy task.…”
mentioning
confidence: 99%